Correlation of Serum Vitamin D and Metabolic Disturbances in Polycystic Ovarian Syndrome - Shasya Aniza Santoso; Tita Husnitawati Madjid; Anita Rachmawati (Indonesian Journal of Obstetrics & Gynecology Science, 2021)
Objective: This study was aimed to determine the correlation between vitamin D and insulin resistance in women with PCOS. Method: This study was correlational analytic with cross-sectional approach to 34 women diagnosed with PCOS based on ultrasonography. Waist circumference and fasting blood glucose (FBG) represented insulin resistance. Women with hormonal therapy and vitamin D supplementation were not included to this study. This study used consecutive sampling method.Result: The average of age was 25.6±6.1 years old. Waist circumference and fasting blood glucose (FBG) represented insulin resistance. The average of waist circumference and FBG were 87.6±12.4 cm and 86.2±27.9 mg/dl, respectively. The mean of vitamin D levels was 11,5±3,6 ng/ml. According to Spearman’s correlation, vitamin D levels were weak negative correlated with waist circumference (r=-0.2; p>0.05) and FBG (r= -0,1; p>0,05), it statistically was not significant.Conclusion: There is weak negative correlation between vitamin D and metabolic syndrome in PCOS patients.Korelasi Kadar Vitamin  D Serum dan Gangguan Metabolik pada Sindrom Ovarium PolikistikAbstrakTujuan: Penelitian ini bertujuan untuk menganalisis korelasi vitamin D dengan resistensi insulin pada pasien dengan SOPK.Metode: Penelitian ini merupakan penelitian analitik korelatif dengan pendekatan potong lintang pada 34 subjek penelitian yang didiagnosis SOPK berdasarkan pemeriksaan ultrasonografi (USG). Lingkar pinggang dan kadar glukosa darah puasa (GDP) diambil sebagai parameter resistensi insulin. Pasien dengan terapi hormon dan suplementasi vitamin D tidak termasuk dalam subjek penelitian. Pengambilan sampel menggunakan teknik consecutive sampling.Hasil: Rerata usia subjek penelitain ini adalah 25,6±6,1 tahun. Lingkar pinggang dan glukosa darah puasa (GDP) diambil sebagai parameter resistensi insulin. Pada penelitian ini subjek memiliki rerata lingkar pinggang 87,6±12,4 dan GDP 86,2±27,9 mg/dl. Rerata kadar vitamin D subjek 11,5±3,6 ng/ml. Berdasarkan uji korelasi Spearman, kadar vitamin D berkorelasi negatif lemah dan tidak signifikan secara statistik baik dengan lingkar pinggang (r= -0,2; p>0,05) maupun dengan GDP (r= -0,1; p>0,05). Kesimpulan: Vitamin D berkorelasi negatif lemah dengan parameter gangguan metabolik resistensi insulin pada pasien SOPK.Kata kunci: sindroma ovarium polikistik, vitamin D, resistensi insulin, sindroma metabolik